The Impact of Start-up Grants on Firm Performance in Estonia - Vildo, Siret; Masso, Jaan (Estonian Discussions on Economic Policy, 2009)
As in economic theory start-up enterprises have been seen as important sources of growth, the government support measures to enterprises have been a common practice around the world for decades. As the governmental support to enterprises is often of a considerable amount of money there is a need to assess its efficiency. In the present article we study the impact of Estonian start-up grants distributed in 2002 and 2003 on various indicators of firm performance with econometric methods, namely propensity score matching. We use the data from the Estonian Business Register in order to study the impact of start-up grants on various economic indicators like the number of employees, turnover, equity, fixed assets and firm survival. The results showed that the start-up grants proved to affect positively the number of employed people and turnover, yet the impact on productivity was negative. One implication of the study is that it is difficult to achieve different goals to the same extent with a single governmental grant